Ozonation in a cold room during the partial maturation of parmesan cheese (Research, Society and Development, 2021)
Microbial contamination can occur during cheese production, and lack of common hygiene contributes to the contamination. Cheese maturation chambers also stand out in favoring fungal multiplication, due to their temperature and humidity conditions, the growth of fungi in parmesan cheese being harmful to both its composition and its structure and appearance, which can lead to rejection by the consumer, causing economic loss in addition to the waste of raw materials. Thus, ozone was used in the maturation of Parmesan cheese, in order to control fungal growth. Analyzes of water activity, color and microbiological analyzes were carried out for 90 days. The gas had no influence on the water activity of the cheeses, whereas in the color results it was found that there was no significant difference only for the 90-day measurements. For the results of coliforms at 35 and 45°C, staphylococci and Salmonella, values were found that met the specifications. Regarding the results of molds and yeasts, ozone managed to reduce the count in the ripening environment.